Novelties in “incertae sedis” Vriesea (Bromeliaceae: Tillandsioideae): Redescriptions, new combinations and nomenclatural revision - Kessous, Igor M.; Costa, Andrea F. (Phytotaxa, 2023)
Revisions of Tillandsioideae have divided the genus Vriesea into nine genera since its last monograph, published in Flora Neotropica. Despite these efforts, the taxonomic placement of some species remains uncertain. We review the 21 species of Vriesea “incertae sedis”, to assist in a new circumscription of this genus and contribute to the nomenclatural stability of related taxa. We present 17 redescriptions, eight new combinations, two lectotypifications, one revalidation, and notes for the all taxa.